PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, LEVERAGE, DAN STRUKTUR KEPEMILIKAN TERHADAP AGRESIVITAS PAJAK - Dewi Setyoningrum; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2019)
The study aims to examine whether corporate social responsibility, firm size, leverage, foreign and public ownership structure affect on the tax aggressiveness. Tax aggressiveness is downward management of taxable income through tax planning activities. Population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2014-2017. Samples in this study are 100 companies, that were collected by using purposive sampling method based on certain criteria. The method of analysis used is multiple regression. The results show that firm size and public ownership have significant  effect to the tax aggressiveness. These results prove that the larger of firm size and public ownership, the greater possibility of the company’s tax aggressiveness. On the other hand, corporate social responsibility, leverage, and foreign ownership does not have significant effect to tax aggressiveness. This results indicate that the higher corporate social responsibility, leverage and foreign ownership cause the possibility of companies not to behave aggressively in taxes.